A Framework for the Selection of an Entry Mode into International Markets for Practical Green Energy Limited - Grandeur, Benedicta (2014)
Given the global reality of businesses this day, the world even though it may seem a small place still necessitate the requirement of a strategic plan, and to evaluate and implement an entry into a foreign market where that market is not indigenous to the parent company because of the inherent political risk, financial risk, and foreign exchange risk of repatriation of funds. Should this evaluation not be carried out, which will form the basis of the strategic decision making with regard to a foreign investment, then the company’s whole investment plan could be at stake.